Relationship between clinical performance and professional self-concept in critical care nurses - Eskandari Narges; Abbasi Mohammad; Abbasinia Mohammad; Norouzadeh Reza (Sciendo, 2021)
To determine the relationship between clinical performance and professional self-concept in critical care nurses.